PENGARUH SISTEM KERJA, PROSEDUR KERJA, DAN KEJELASAN JOB DESK BAGI KARYAWAN TERHADAP TINGKAT PRODUKTIVITAS KARYAWAN PADA PT. INFINITE GLOBAL OTO CABANG MEDAN - Khomeiny Yunior; Davin Davin; Salim Salim (Universitas Methodist Indonesia, 2021)
The purpose of this research is to examine the effect of working system, working procedures, job desk for employees on the productivity of employees in PT. Infinite Global Oto Cabang Medan of partial and simultaneous. Employee productivity decline marked by not reaching its sales target set by the working system caused by inadequate and procedures of work and job desk employee. Population is 70 employees and in the study were included in the study were 70 employees. The methodology use multiple linear regression analysis techniques. The results of the study working system and procedure of a work as a partial did not affect productivity employees in PT Infinite Global Oto Cabang Medan. Job desk in partial influence employee productivity in PT. Infinite Global Oto Cabang Medan. Working system, working procedures and job desk job simultaneously influences employee productivity.